ANALISIS KEKERASAN YANG DIALAMI IQBAL RAMADHAN DITINJIAU DARI PERSPEKTIF PANCASILA SILA KEDUA - Nora Divina Ramadani Ramadani (Fakultas Keguruan dan Ilmu Pendidikan Program Studi Pendidikan Pancasila dan Kewarganegaraan, 2024)
This research analyzes the violence experienced by Iqbal Ramadhan, an assistant lawyer, during a demonstration against the Revision of the Regional Election Law in Jakarta. The repressive actions by security forces against Iqbal, which included physical and psychological violence, showed a deviation from the principle of